Early growth of invasive acacias as a potential biomass-for-energy source under Mediterranean conditions. (2016) - Carneiro, Marta; Moreira, Rita; Gominho, Jorge; Abreu, Francisco; Fabião, António
Most of the short rotation energy coppices used in Northern and Central Europe may be of limited value under Mediterranean climates. Abandoned acacia stands with an invasive behaviour, of environmental concern in many Mediterranean countries, may perform better as biomass producers under summer drought than those coppices. Seedlings of invasive Acacia dealbata, A. melanoxylon and A. pycnantha were planted to test for early growth performance under rain-fed and irrigated conditions. Rooted cuttings of an E. globulus clone were also established as a reference for biomass production. Plants were harvested after one year, sorted by biomass components and oven-dried. Above-ground dry weight was calculated on an area basis, accounting for survival. A. dealbata and A. melanoxylon showed low survival and biomass production, even irrigated, whereas A. pycnantha had better survival and growth performance than eucalypt, even in rain-fed plots, suggesting potential for the harvest of this drought-adapted species as a biomass source.